The analysis of individual legislative initiatives that are aimed at protecting copyright and related the Internet - Зеленов, Геннадій Михайлович; Зеленова, Марина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article discussed the draft laws designed by the Cabinet of Ministers of Ukraine directed on protection of copyright and related rights in the Internet. Determined that these bills are designed to implement the Association Agreement between Ukraine, on the one hand, and the European Union, the European atomic energy community and their member States, on the other hand. The article States that submitted to the VerkhovnaRada of Ukraine the draft laws in this sphere are identical in their content. The refore, this article focuses on the fact of them, which is now under consideration of the VerkhovnaRada of Ukraine. This law draft has the registration No. 4629. Law draft No. 4629 proposes to amend the Code of Ukraine on administrative offences and the Laws of Ukraine «On notary», «On copyright and related rights», «On telecommunications». In particular, the Law of Ukraine «On copyright and related rights».The article focuses on the amendments to the Code of Ukraine on administrative offences and the law of Ukraine «On copyright and related rights», the advantages and disadvantages of these changes and the ways of perfection of such changes. In particular, noted that the proposed draft law a mechanism of protection of the copyright and/or related rights, it is proposed to introduce in the Law of Ukraine «On copyright and related rights», it creates the opportunity for a longer block information, which is stored in the Internet. This mechanism can be used for wrongful blocking of certain information, which is posted on the web site. However, no liability for such actions predict not offered.